Chlorophyll content and antioxidant activity of sunflower oil with aromatic raw materials - Usatyuk, Svitlana; Pelekhova, Lyubov (My University, 2014)
The article presents the results of the study on chlorophyll content and antioxidant activity of sunflower oil with aromatic raw materials. Dried parsley and basil were used as aromatic raw materials. Dried basil and parsley were in the amount of 2 to 10 %. The chlorophyll content was quantified by the photometric method. Determination of the AOA was carried out by the Flourescence Recovery after Photobleaching (FRAP) method.
Keywords: chlorophyll content; вміст хлорофілу; antioxidant activity; антиоксидантна активність; aromatic raw materials; пряно-ароматична сировина; basil; базилік; parsley; петрушка; sunflower oil; соняшникова олія; кафедра експертизи харчових продуктів